Succession to Kingship in the Bapedi Ethnic Group – Cultural Intricacies of Post-conquest South Africa and the Impact of the Constitution - Ntsoane, Lefa; Manthwa, Aubrey (Journal of Law, Society and Development, 2022)
African kingdoms have existed for centuries predating colonialism and continue to be significant despite assertions that they are autocracies. These claims stem from the fact that kings do not ascend to power through Western democratic means such as elections. Democracy, however, exists in African kingdoms, because communities are afforded opportunities to participate in decision-making. Furthermore, African kingships are often accused of patriarchy since women are not always allowed to ascend to royal thrones. This critique of African kingships is rather hypocritical, because Europe is the bedrock of patriarchy, but this is ignored when accusations are levelled at African kingdoms. The biggest problem that kingdoms in South Africa experience today is that they do not enjoy the separate and independent identity that they enjoyed in the past since they are now subject to the Constitution as the supreme law of the land. This state of affairs is problematic as it denies South Africa a decolonial option and does not achieve restorative justice. The move to a constitutional democracy has led to considerable changes in South Africa, such as the dissipation of important roles that African-style courts used to fulfil, and the powers enjoyed by kings may also wane because of a lack of title to sovereignty over their kingdoms. This article discusses the right of succession to kingship in the light of the Bapedi Kingdom succession dispute, where the Commission on Traditional Leadership Disputes and Claims and courts recognised the descendants of Kgosi Sekhukhune as the rightful successors to the Bapedi throne. This ruling was important because the usurpation of the throne through bloodshed, although not common, was recognised as a legitimate way to usurp kingship.